2016
DOI: 10.3892/ol.2016.5394
|View full text |Cite
|
Sign up to set email alerts
|

CRKL overexpression promotes cell proliferation and inhibits apoptosis in endometrial carcinoma

Abstract: The v-Crk avian sarcoma virus CT10 oncogene homolog-like (CRKL) protein is important in cancer progression. However, its expression pattern and biological roles in human endometrial carcinoma remain unexplored. The potential mechanism of CRKL-induced cancer progression is still unclear. The present study aimed to explore the expression pattern and biological roles of CRKL in human endometrial carcinoma. Using immunohistochemistry, it was observed that the CRKL protein was overexpressed in 50.5% (44/87) of endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Our recent study has demonstrated that CRKL (22q11) is seldomly but recurrently amplified in laryngeal squamous cell carcinoma 8 . Morover, CRKL is known to be overexpressed in a number of different cancer types, including these of breast 19,20 , gastric 21,22 , endometrial carcinoma 23 and lung 24,25 . Overepression of CRKL is also present in colorectal cancers 26 www.nature.com/scientificreports www.nature.com/scientificreports/ and cervical cancer samples 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study has demonstrated that CRKL (22q11) is seldomly but recurrently amplified in laryngeal squamous cell carcinoma 8 . Morover, CRKL is known to be overexpressed in a number of different cancer types, including these of breast 19,20 , gastric 21,22 , endometrial carcinoma 23 and lung 24,25 . Overepression of CRKL is also present in colorectal cancers 26 www.nature.com/scientificreports www.nature.com/scientificreports/ and cervical cancer samples 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Endometrioid carcinoma is the commonest subtype of endometrial carcinoma which is considered one of the commonest gynecological cancers worldwide [2]. Former researchers showed that disordered expression of certain proteins in endometrioid carcinoma tissues could contribute to its progression and malignant behavior [2], but novel bio-markers which are responsible for malignant initiation and progression and that which predict the aggressive behavior have been still urgently needed aiming at discovering novel targeted therapy. CRKL protein was found to be upregulated in many cancers, moreover, CRKL amplification was observed in bronchogenic carcinoma, colorectal cancer and pancreatic cancer [2].…”
Section: Discussionmentioning
confidence: 99%
“…We have incubated sections which were cut and put on positively charged slides with anti-CRKL rabbit polyclonal antibody ( The intensity of both CRKL and CK2 β staining was given scores from 0 -3; 0 Open Journal of Obstetrics and Gynecology The scores of each tumor sample have been multiplied to reach a final stain score of zero-12. We consider 5 as a cut point to differentiate between CRKL and CK2 β low expression which is less than 5 total stain score and tumor samples scoring 5 -12 were considered to exhibit CRKL and CK2 β overexpression [2]. Stratification of RFS, PFS, DMFS, and OS was done according to CRKL and CK2 β expression.…”
Section: Immunohistochemistry Technique Of Staining and Evaluation Ofmentioning
confidence: 99%
See 2 more Smart Citations